2018
DOI: 10.1016/j.chest.2017.09.031
|View full text |Cite
|
Sign up to set email alerts
|

Three-Hour Bundle Compliance and Outcomes in Patients With Undiagnosed Severe Sepsis

Abstract: Severe sepsis continues to be an underdiagnosed and undertreated condition. Patients who were diagnosed had higher treatment rates yet experienced worse outcomes. Continued investigation is needed to identify factors contributing to diagnosis, treatment, and outcomes in patients with severe sepsis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 16 publications
(20 reference statements)
2
21
0
1
Order By: Relevance
“…A recent study has shown that nearly half of patients with severe sepsis (which is similar to the more recent definition of sepsis evaluated in this study), lack sepsis-specific International Classification of Disease (ICD) codes. This study additionally showed that patients with sepsis-specific ICD codes were more likely to receive appropriate sepsis treatment [29]. The significant advance lookahead time provided by this MLA allows for improved risk-stratification of patients, with increased monitoring or more frequent care team assessment for patients with high risk scores.…”
Section: Discussionmentioning
confidence: 73%
“…A recent study has shown that nearly half of patients with severe sepsis (which is similar to the more recent definition of sepsis evaluated in this study), lack sepsis-specific International Classification of Disease (ICD) codes. This study additionally showed that patients with sepsis-specific ICD codes were more likely to receive appropriate sepsis treatment [29]. The significant advance lookahead time provided by this MLA allows for improved risk-stratification of patients, with increased monitoring or more frequent care team assessment for patients with high risk scores.…”
Section: Discussionmentioning
confidence: 73%
“…Next, we must consider whether this relationship between time to antibiotic and mortality causative or only a correlation, given that all other components of the sepsis care bundle may be potentially physiologically effective along with time to antibiotic and that the effectiveness of each component remains controversial in various settings [10, 20, 21]. Adherence to the sepsis care bundle also varies in each setting [8, 10, 22, 23]. For example, in a study among patients who received antibiotics as they met the criteria for severe sepsis, a relatively high compliance rate for the sepsis care bundle was reported if sepsis was definitively diagnosed (with diagnosis code) compared with undiagnosed sepsis (without diagnosis code) [22].…”
Section: Discussionmentioning
confidence: 99%
“…Studies cite wide variations in compliance, with some reporting it to be as low as 8.7%. 9,10 Of the 4 performance measures included in the 3-hour bundle, repeated lactate measurement was met least often. 10 As discussed, we are unable to state that a lactate-guided approach is inferior to a peripheral perfusion approach, and it is safe to say it is no better.…”
Section: Discussion Pointsmentioning
confidence: 99%